2004
DOI: 10.1021/jp0485035
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Platinum Clusters:  Planar or Spherical?

Abstract: Platinum clusters of up to 55 atoms were studied using density functional theory with a plane wave basis set. The results show that planar platinum clusters of up to nine atoms are as stable as their three-dimensional isomers and the six-atom planar cluster is, surprisingly, more stable than its three-dimensional isomers. Among the three-dimensional platinum clusters investigated in this work, the layered clusters are found to be as stable as their spherical close-packed isomers. The high stability of planar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
230
5
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(285 citation statements)
references
References 56 publications
46
230
5
4
Order By: Relevance
“…We see that the cage-like geometries show a more structured DOS, with well defined peaks. This is probably due to a higher geometrical symmetry (O h for Au 18 and T d for Au 20 ), as shown in a previous work for Au 55 10 . This fact is independent of the GGA or LDA level of theory.…”
Section: Au18supporting
confidence: 57%
See 1 more Smart Citation
“…We see that the cage-like geometries show a more structured DOS, with well defined peaks. This is probably due to a higher geometrical symmetry (O h for Au 18 and T d for Au 20 ), as shown in a previous work for Au 55 10 . This fact is independent of the GGA or LDA level of theory.…”
Section: Au18supporting
confidence: 57%
“…However, although Pt shows as strong relativistic effects as Au 2 , it has been shown that the competition between planar and 3D structures of Pt clusters is not affected by relativistic effects 18 . Notice that Pt 7 is three-dimensional (3D) 19,20 , like Ag 7 or Cu 7 , but Au 7 is planar.…”
Section: Introductionmentioning
confidence: 99%
“…1 The surface of clusters can completely change their physical properties. Therefore, metallic clusters are technologically important for their catalytic activity and also play a major role in catalysis, colloidal chemistry, and medical science.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest energy structural isomer found for Pt19 + has an octahedral shape, which has also been predicted computationally for neutral Pt19. [24] Isomers for XPt18 + are explored by substituting inequivalent sites of Pt19 + with the dopant atom, followed by local structural optimization. The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 COMMUNICATION obtained minimum energy structures are shown in Figure 2.…”
mentioning
confidence: 99%